The Impact of Corporate Governance on Profitability of Conventional Banks Operating in Pakistan - Hafiz Muhammad Naveed; Shoaib Ali; Yao Hongxing; Saqib Altaf; Jan Muhammad Sohu (Yayasan Ahmar Cendekia Indonesia, 2020)
The key purpose of present research study to examine the association among corporate governance and profitability banks in developing counties. For such primary objective, annually based data collected from 2004 to 2016. The data taken from annual financial reports which issued by conventional banks. We have used ADF (Augmented Dickey Fuller) test to examine the unit-root of variables. Moreover, the multiple linear regression utilized for hypothetical estimation. The results indicates that corporate governance and conventional banks profitability of Pakistan are bidirectional (positive-negative) associated to each other. In addition, the board size (Board Directors) is negatively associated with Return on assets and return on equity of banks. Similarly, the board independence (Insider-Outsider Board Directors) is positively influenced to return on assets and return on equity of conventional banks of Pakistan. The overall findings shows that board size and board independence are highly associated with return on equity than return on assets. Moreover, banking sector in developing countries the board size should contain on appropriate strength and acquire more professional and qualified staff. An optimal number of directors in a board size there is a need of commercial banks as to increase the profitability. To enhance the investors’ confidence with the bank there is also a need of the commercial banks to increases the board independency.